Pelatihan Kewirausahaan dan Inovasi Berbasis Digital pada Pemuda Desa Sambigede dalam Mendukung Percepatan Pengembangan Kawasan Desa Wisata - Dediek Tri Kurniawan; Slamet Fauzan; Rizky Firmansyah; Andro Agil Nur Rakhmad (STKIP Andi Matappa, 2022)
This service aims to provide entrepreneurship training for youth in Sambigede Village, Sumberpucung District, Malang Regency. The competencies targeted are in the entrepreneurial concept of administrative competency, knowledge and technology, communication skills, network building competency, business model development competency, creativity and innovativeness and attaining finance capability. The training is designed in two stages with training participants (users) namely village youth who are members of the Sari Kusuma Negara Karang Taruna Management (SAKURA) and MSME actors. The purpose of this training is an understanding of the concept of a tourist village, the use of information technology, and capacity building for entrepreneurial competencies. At the end of the training, participants are able to map out tourism potential and understand the concept of entrepreneurship, opportunities for using technology, and the concept of a tourist village. The training participants are also able to create concept ideas and innovations to capture opportunities from the potential of Sambigede Village as a tourist village.